What Universities Owe Democracy - Pelton, M. Lee (Journal of Economic Literature, 2024)
M. Lee Pelton of The Boston Foundation reviews “What Universities Owe Democracy” by By Ronald J. Daniels. The Econlit abstract of this book begins: “Promotes the argument that colleges and universities are essential to the flourishing of liberal democracy, suggesting that these institutions have a responsibility to act in defense of the liberal democratic experiment.”